The Correlation Between Students’ Interest and Students’ Achievement in Learning English - Widharmawanta Ginting; Risnawaty Risnawaty; Harianto Harianto (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
The article aims to investigate whether there is significant correlation between students’ interest and students’ achievement in learning English at SMA Swasta Pertiwi Medan. The techniques used to collect the data are observation and questionnaire. The researcher selected 30 students as a sampling from Grade X IA2. The Finding of the study is the students’ interest could influence the in achievement. Students who have high interest try to pursue knowledge more than who have the low one. They tend to be more attentive in learning the lesson and motivation to enrich their vocabulary, to practice their English and do a lot of exercises to make them more skillful in using English. Based on the research finding, the conclusion is that there is a correlation between students’ interest and their achievement. it is suggested to (1) to teacher who teaches English in the classroom need to ensure that student realize that both high and low interest gets attention, (2) the teacher has to manage the classroom to help the students think creatively